2021
DOI: 10.1007/s10965-021-02538-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cross-linked polyurethane elastomers with the inclusion of polar-aromatic moieties (BA, PNBA and 3, 5-DNBA): Electrical and thermo-mechanical properties analysis

Abstract: In this work, we used the design strategy “doped nonpolar polymers” and synthesized the polyurethane elastomers (PUEs) by doping with highly polar aromatic molecules such as benzoic acid (BA), 4(para)-nitro-benzoic acid (PNBA), and 3, 5-di-nitro-benzoic acid (3, 5-DNBA) by using the solution casting method. The effect of each molecule in three different weight percentages 2%, 4%, and 6% on electrical and thermo-mechanical properties of the material has studied. Experiments were carried out to determine electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
3
6
0
Order By: Relevance
“…Both observed effects due to the addition of acid and COOH-functionalized MWCNTs could be attributed to the elimination of the foaming phenomenon in the BPC. Data obtained here are in agreement with the findings of other researchers [2,55] that reported how the introduction of a small dosage of a strong acid, such as HCL, prohibited the formation of PU; while the implementation of a weaker acid, such as acetic acid and benzoic acid, has a less pronounced inhibiting effect. Notwithstanding, the addition of COOH-functionalized MWCNTs not only promoted the crosslinking density of the PU specimen containing acid but also led to more crystallinity in the sample.…”
Section: Microstructural Chemical and Carbon Footprint Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…Both observed effects due to the addition of acid and COOH-functionalized MWCNTs could be attributed to the elimination of the foaming phenomenon in the BPC. Data obtained here are in agreement with the findings of other researchers [2,55] that reported how the introduction of a small dosage of a strong acid, such as HCL, prohibited the formation of PU; while the implementation of a weaker acid, such as acetic acid and benzoic acid, has a less pronounced inhibiting effect. Notwithstanding, the addition of COOH-functionalized MWCNTs not only promoted the crosslinking density of the PU specimen containing acid but also led to more crystallinity in the sample.…”
Section: Microstructural Chemical and Carbon Footprint Analysissupporting
confidence: 92%
“…The isocyanate used was solvent-free, medium-viscosity polymethylene polyphenyl polyisocyanate, Lupranate M70L (BASF, Wyandotte, MI, USA) with NCO content of 31.0 wt.%. Several trial mixes were designed and tested to identify, examine and overcome the challenges of producing BPC, including excessive foaming, fast setting, and zero flowability, as depicted in Figure 1a-c It was suggested that when the mix acidity is increased, foam formation can be stopped due to the blockage of the active -NCO sites of polyisocyanate [2]. It was also shown that acids with the 𝑝𝐾 𝑎 in the range of 2.8-4.5 will retard rather than prohibiting the polymerization of PU [34].…”
Section: Materials and MIX Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows a schematic of the materials system and the generation of polarization and piezoelectricity. [ 109 ] When a compressive force is applied to these foams, the dipole moment density increases due to fixed guest dipoles, inducing a surface charge and hence current flow. The fabrication approach could be used for other materials having greatly low bulk moduli for example brush polymers.…”
Section: Types Of Polymeric Piezoelectric Foamsmentioning
confidence: 99%
“…Polyurethane is a type of polymer that could be manufactured and used in a wide range of applications, including elastomer, thermosetting glue, rigid polyurethane, foam, etc. [ 34 ] The formation of hard segments (HS) and soft segments (SS) in polyurethane's structure is its special aspect. Short diols and isocyanates from the hard segments, while long polyols create the soft segments.…”
Section: Introductionmentioning
confidence: 99%